1990
DOI: 10.3382/ps.0691787
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Antibiotics on Performance, Processing Characteristics, and Parts Yield of Broiler Chickens

Abstract: Broilers were grown to 49 days of age on diets supplemented with bambermycins (BAM, 2.2 ppm), bacitracin methylene disalicylate (BMD, 27.5 ppm), virginiamycin (VM, 11 ppm), or an unmedicated control. Samples of birds were processed for dressing percentage and parts yield. There were no significant (P greater than .05) effects of antibiotics on final body weight, feed conversion, or mortality. In male broilers, BMD and VM significantly (P less than or equal to .05) increased dressing percentage and percentage y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 11 publications
1
10
2
1
Order By: Relevance
“…The VM by E interaction approached significance (P = 0.07) for dressing percentage, suggesting that within the TN environment 15 ppm VM improved (P = 0.07) dressing percent compared with the control and 20 ppm VM supplementation. Izat et al (1989) reported no effect of 11 ppm VM on carcass weight or dressing percentage; however, according to the results of the current study and others (Leeson, 1984;Woodward et al, 1988;Izat et al, 1990) the VM influence on carcass variables is consistent. A reduction of intestinal weight, as a result of antibiotic supplementation have been reported in previous studies (Coates et al, 1955;Jukes et al, 1956;Henry et al, 1986;Izat et al, 1989).…”
Section: Resultssupporting
confidence: 74%
“…The VM by E interaction approached significance (P = 0.07) for dressing percentage, suggesting that within the TN environment 15 ppm VM improved (P = 0.07) dressing percent compared with the control and 20 ppm VM supplementation. Izat et al (1989) reported no effect of 11 ppm VM on carcass weight or dressing percentage; however, according to the results of the current study and others (Leeson, 1984;Woodward et al, 1988;Izat et al, 1990) the VM influence on carcass variables is consistent. A reduction of intestinal weight, as a result of antibiotic supplementation have been reported in previous studies (Coates et al, 1955;Jukes et al, 1956;Henry et al, 1986;Izat et al, 1989).…”
Section: Resultssupporting
confidence: 74%
“…Antibiotic growth promoters have been helpful in improvement of growth performance and feed conversion ratio in poultry (Miles et al, 2006;Dibner and Buttin, 2002;Izat et al, 1990). However, constant treatment of poultry by antibiotic may result in residues of these substances in poultry products and bacteria resistance against treatments in human body.…”
Section: Introductionmentioning
confidence: 99%
“…Added in low doses to the feed of farm animals, they have been shown to increase daily weight gain and conversion of feed into body mass, leading to economic advantages for farmers 2,3,4,5 . However, there is an increasing trend to reduce this use of antibiotics in feedstuffs.…”
Section: Removing Antimicrobial Growth Promoters and The Rise Of Necrmentioning
confidence: 99%